(untitled) (REMUNOM, 2025)
Sports psychology has shown growing interest in motivation for sports and its specific dimensions. This study aimed to analyze the dimensions that motivate visually impaired students to practice Paralympic judo. The research adopted a quantitative, descriptive, and cross-sectional approach, involving 17 students, seven of whom were female, all from the Solidariedade Secondary School (Maputo city). Data were collected using the Gaya and Cardoso (1998a) Sports Motivation Inventory and analyzed using nonparametric descriptive and inferential statistics (Mann-Whitney U test). The results indicated that the dimension most valued by participants was "Friendship/Leisure" (2.43 ± 0.31), with "Health" (1.92 ± 0.16) being the least valued. No statistically significant differences were observed based on gender or previous sports practice. It is concluded that the visually impaired students in this study engage in sports primarily for social and recreational reasons, prioritizing interaction and leisure over competition or health benefits. These results contribute to the planning of inclusive sports programs that consider the specific interests and motivations of this target group